Inotuzumab ozogamicin in infants and young children with relapsed or refractory acute lymphoblastic leukaemia: a case series. (2nd February 2021) - Brivio, Erica; Chantrain, Christophe F.; Gruber, Tanja A.; Thano, Adriana; Rialland, Fanny; Contet, Audrey; Elitzur, Sarah; Dalla‐Pozza, Luciano; Kállay, Krisztián Miklós; Li, Chi‐kong; Kato, Motohiro; Markova, Inna; et al.
Summary: No data on inotuzumab ozogamicin (InO) in infant acute lymphoblastic leukaemia (ALL) have been published to date. We collected data internationally on infants/young children (<3 years) with ALL treated with InO. Fifteen patients (median 4.4 months at diagnosis) received InO due to relapsed or refractory (R/R) disease. Median percentage of CD22 + blasts was 72% (range 40–100%, n = 9). The median dose in the first course was 1.74 mg/m 2 (fractionated). Seven patients (47%) achieved complete remission; one additional minimal residual disease (MRD)‐positive patient became MRD‐negative. Six‐month overall survival was 47% (95% confidence interval [CI] 27–80%). Two patients developed veno‐occlusive disease after transplant. Further evaluation of InO in this subgroup of ALL is justified.